Conflicts between transport policies and spatial development policies: perspectives on regional cohesion in the European Union - Roger Vickerman (European Regional Science Association (ERSA), 2004)
The development of the Trans-European Networks (TENs) in the EU is one of the first attempts at achieving a top-down approach to the development of a genuine European network in the interests of greater competitiveness and cohesion in the European economy. This implies the need for consistency with both national transport policies and with other EU policies, such as those on the environment, regional development and stability and growth. This paper explores the interaction between these policy areas to assess the extent of horizontal co-ordination between different sectoral policies and vertical co-ordination between different policy levels. The analysis of horizontal co-ordination has three main elements: the identification of horizontal spillovers between policy areas; the analysis of how policy responds to the evidence of horizontal spillovers; and the organisational structures put in place to implement policy. A key to this is the distinction between identifying spillovers between policy areas or establishing co-ordination between them as an aim of policy and the implementation of detailed policy objectives and measures to address such matters. This is achieved by examining the extent to which spillovers are recognised in key policy documents and the way this has shaped the policy design and its implementation. As well as the horizontal links between different EU policy areas, the analysis of vertical co-ordination involves enquiring into the relationships between different levels of government and decision making. This addresses the question as to how higher levels of government establish a policy environment within which lower levels operate. This has three main dimensions: the way in which policy is framed to establish the goals which need to be addressed by the lower levels of decision making (top-down policy formation); the extent to which the formation of policy by higher level bodies is informed by and takes cognisance of the views and needs of lower level bodies (bottom-up policy formation); and the way in which high levels of government monitor and police decisions by lower level bodies. The paper provides a schematic framework for analysing policy interaction developed from research as part of the ESPON programme of the EU which identifies opportunities for greater coherence and the risks of conflict. The paper suggests that ignoring these conflicts places the opportunity for further cohesion in regional development in the EU at risk.
Keywords: 330